Cost Analysis of Cancer Side Effects Therapy in Cancer Patients in Rumah Sakit Prof. Dr. Margono Soekarjo Purwokerto - Pradana, Febrian; Purwonugroho, Tunggul Adi; Ekowati, Heny (Indonesian Research Gateway, 2012)
Cancer Â is Â the Â leading Â cause Â of Â death Â in Â Indonesia. Â Generally, Â cancer Â therapy Â useÂ chemotherapy, Â radiation, Â surgery Â or Â combination Â of Â those. Â Various Â side Â effects Â caused Â byÂ cancer Â therapy Â make Â the Â use Â of Â additional Â drugs. Â This Â leads Â to Â an Â increase Â in Â total Â costÂ incurred Â to Â cancer Â patients. Â The Â purpose Â of Â this Â study Â was Â to Â describe Â the Â treatment Â ofÂ cancer Â therapyâs side effects Â as Â well Â as Â the Â average Â cost Â of Â side Â effects Â treatment, Â and Â itsÂ percentage Â in Â the Â total Â cost Â of Â cancer Â patients Â in Â Rumah Â Sakit Â Margono Â Soekarjo. Â ThisÂ research was a descriptive study with retrospective data Â by total sampling method obtainedÂ from Â patientsâ Â medical Â and Â receipts Â records Â of Â five Â most Â common Â cancers Â (breast,Â nasopharynx, Â Non Â Hodgkins Â Lhympoma Â (NHL), Â ovarian, Â and Â cervix) Â during Â January-December 2010. The average cost of Â patientâs side effects treatment was calculated by theÂ average Â cost Â of Â side Â effects Â compared Â to Â the Â average Â total Â direct Â costs Â incurred Â to Â cancerÂ patients. Â The Â samples Â was Â obtained Â from Â the Â population Â of Â 2261 Â patients Â who Â met Â theÂ inclusion criteria, that are 73 patients consist of 62 female patients and 11 male patients. TheÂ most Â common Â side Â effects Â of Â cancer Â therapy Â were Â nausea Â and Â vomiting Â (59.80%), Â nausea-vomiting, Â anemia, Â and Â pain Â (16.44%), Â and Â nausea-vomiting Â and Â anemia Â (15.07%). Â The Â mostÂ used therapy was vitamin B complex followed by histamine-2 inhibitor. The average cost ofÂ side effects for breast cancer was Rp 1,715,373 (8.73%), nasopharynx was Rp 1,149,049 (6.98Â %); Â NHL Â was Â Rp Â 360,778 Â (1.97 Â %); Â ovary Â was Â Rp Â 911,118 Â (3.61 Â %) Â and Â cervical Â was Â RpÂ 1,416,027 (8.87 %). The results indicated Â that the hospital needs Â to pay Â more attention Â onÂ nausea-vomiting effect of chemotherapy, and also cervical cancer side effects therapy as theÂ most costly.Keywords: Cost Analysis, Cancer, Side Effects, Prof. Dr. Margono Soekarjo Hospital